2022
DOI: 10.1155/2022/1393177
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Knockdown of PVT1 Exerts Neuroprotective Effects against Ischemic Stroke Injury through Regulation of miR‐214/Gpx1 Axis

Abstract: Previous studies have reported that lncRNA PVT1 was closely related to ischemic stroke. Here, the role of PVT1 in ischemic stroke and the underlying mechanism were investigated. OGDR-stimulated PC12 cells were used to construct a cell model to mimic ischemic stroke. si-PVT1, miR-214 mimic, inhibitor, or the negative controls were transfected into PC12 cells prior to OGDR treatment. PVT1, miR-214, and Gpx1 expression was measured by qRT-PCR and western blotting assays. Cell proliferation and apoptosis were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%